Rare bird documentation form for Northern Goshawk at Hartman Reserve, 1983 - Staudt, Thomas J.et al (1983)
Rare bird documentation form for a Northern Goshawk at Hartman Reserve in Black Hawk County, IA on November 26, 1983. Epson - sheet feed